Marginalization and social change processes among lesbian, gay, bisexual and transgender persons in Swaziland: implications for HIV prevention. (20th June 2018) - H. Logie, Carmen; Perez-Brumer, Amaya; Jenkinson, Jesse; Madau, Veli; Nhlengethwa, Winnie; Baral, Stefan
ABSTRACT: Swaziland has among the highest national adult HIV prevalence globally. There is limited knowledge of HIV vulnerabilities and prevention engagement among lesbian, gay, bisexual and transgender (LGBT) persons in the context of Swaziland's criminalization of consensual same-sex practices. This study explored social processes of marginalization to assess how they could potentiate HIV vulnerabilities and limit engagement in HIV prevention services. Additionally, we assessed positive change to better understand existing strategies employed by LGBT persons to challenge these HIV prevention barriers. Guided by community-based research methodology and conducted in Mbabane and Manzini, Swaziland, data were collected by LGBT peer-research assistants (PRA) in collaboration with an LGBT community organization in Manzini. Semi-structured interviews were conducted by trained PRAs and explored HIV prevention, including experiences of stigma and coping. Audio files were transcribed verbatim, translated to English, and analyzed using thematic techniques. Among participants ( n = 51; mean age: 26.47, SD: 4.68), 40 self-identifed as gay or lesbian (78.4%), 11 bisexual (22.6%), and 12 (23.5%) identified as transgender. Findings highlighted three primary processes of marginalization and positive change in structural, community, and internal domains. First, structural marginalization, which included criminalization, healthcare discrimination, and a scarcity of LGBT tailored HIV prevention resources was challenged by grassroots networks created to access and share specific HIV resources with LGBT persons and the Ministry of Health. Second, community marginalization included stigma and multi-dimensional forms of violence, however, this was met with LGBT persons providing mutual peer support, including for accessing HIV testing services. Thirdly, internal marginalization comprised of self-stigma and associated sexual risk practices was contrasted with coping strategies focused on self-acceptance, stemming from social support and leading to healthcare utilization. Jointly, these findings can inform the implementation of community-based and rights affirming HIV prevention and care cascade strategies that improve coverage of services with LGBT persons in Swaziland.